(untitled) (Psychology Travelogs, 2024)
The article explores the key aspects of professional development as an essential stage of personal growth in the context of modern globalization and digitalization. The transformation of global economic and social processes under the influence of globalization trends and the rapid development of digital technologies significantly reshapes the labor market and the requirements for professional training. In these conditions, professional development becomes not only a process of acquiring specialized knowledge and skills but also a continuous process of personal growth that demands adaptation to new challenges, self-regulation, lifelong learning, and mastering digital competencies. The article analyzes the psychological factors that facilitate or complicate this process, emphasizing the need for developing an individual trajectory for professional growth. In particular, the importance of developing soft skills, which become crucial in conditions of instability and rapid change, is highlighted. The impact of the digital environment on professional development is studied, particularly the increasing role of distance learning, the automation of work processes, and the use of artificial intelligence. The main factors affecting the professional development of individuals in the modern conditions of globalization and digitalization are considered, which are divided into several categories: technological, socio-economic, cultural and individual-psychological. The article also addresses the issue of social responsibility among professionals in the digital environment and the importance of intercultural competence in a globalized world. It concludes that professional development in modern conditions is complex, combining not only the acquisition of professional skills but also the development of personal qualities necessary for a successful career in the digital age.